Highly transparent and reproducible nanocrystalline ZnO and AZO thin films grown by room temperature pulsed-laser deposition on flexible Zeonor plastic substrates. (1st September 2015) - Inguva, Saikumar; Vijayaraghavan, Rajani K; McGlynn, Enda; Mosnier, Jean-Paul
Abstract: Zeonor plastics are highly versatile due to exceptional optical and mechanical properties which make them the choice material in many novel applications. For potential use in flexible transparent optoelectronic applications, we have investigated Zeonor plastics as flexible substrates for the deposition of highly transparent ZnO and AZO thin films. Films were prepared by pulsed laser deposition at room temperature in oxygen ambient pressures of 75, 150 and 300 mTorr. The growth rate, surface morphology, hydrophobicity and the structural, optical and electrical properties of as-grown films with thicknesses ∼65–420 nm were recorded for the three oxygen pressures. The growth rates were found to be highly linear both as a function of film thickness and oxygen pressure, indicating high reproducibility. All the films were optically smooth, hydrophobic and nanostructured with lateral grain shapes of ∼150 nm wide. This was found compatible with the deposition of condensed nanoclusters, formed in the ablation plume, on a cold and amorphous substrate. Films were nanocrystalline (wurtzite structure), c -axis oriented, with average crystallite size ∼22 nm for ZnO and ∼16 nm for AZO. In-plane compressive stress values of 2–3 GPa for ZnO films and 0.5 GPa for AZO films were found. Films also displayed high transmission greater than 95% in some cases, in the 400–800 nm wavelength range. The low temperature photoluminescence spectra of all the ZnO and AZO films showed intense near band edge emission. A considerable spread from semi-insulating to n-type conductive was observed for the films, with resistivity ∼10 3 Ω cm and Hall mobility in 4–14 cm 2 V −1 s −1 range, showing marked dependences on film thickness and oxygen pressure. Applications in the fields of microfluidic devices and flexible electronics for these ZnO and AZO films are suggested.